Peran Radio Komunitas dalam Pemberdayaan Ekonomi Masyarakat: Studi Kasus Rakom Pendowo FM Sidoarjo - Zuhri, Syaifudin; Arif, Rozaqul (Jurnal Komunikasi Islam, 2021)
Community radio in Indonesia has grown rapidly in the past 20 years in line with the raising of public awareness about the right to free access to public information. This study aims to describe the role of community radio as a medium for empowering rural communities, especially in driving the community's economy. Through a qualitative descriptive method, the results of the study show that community radio in Sidoarjo is beneficial for developing the village economy and encouraging micro-enterprises at the village level where small business units grow. In this case, Radio Pendowo FM community as part of the community media has shown its role by synergizing with the community and village government.